Preliminary Exploration of Digital Bigbook Media to Enhance Scientific Literacy among Elementary School Students - Muslimasari, Ella Putri; Susiyawati, Enny; Widodo, Wahono (Journal of Innovation and Research in Primary Education, 2025)
This preliminary study explores the potential of digital Bigbook media to improve scientific literacy among elementary school students in Indonesia, focusing on a case study at UPT SDN 155 Gresik. The research was conducted in response to challenges identified in science instruction, particularly on the topic of the human digestive system, where conventional teaching methods and limited media use have led to low student engagement and conceptual understanding. A qualitative approach was adopted through classroom observations, teacher interviews, and document analysis to identify the current practices and instructional needs. The results reveal that teaching heavily relies on lectures and textbook illustrations, with minimal integration of interactive or visual media. Teachers expressed a strong need for engaging, narrative-based digital media to help students visualize complex scientific processes. Digital Bigbooks, combining storytelling with scientific content and vivid illustrations, are identified as a promising medium that aligns with the principles of meaningful learning and constructivist pedagogy. The findings also highlight the importance of media that supports differentiated learning and reflects the learning styles of digital-native students. This initial exploration provides a foundational insight for the development of a digital Bigbook prototype tailored to elementary science curricula. The study concludes that digital Bigbooks offer a feasible and contextually relevant solution to enhance science learning experiences and scientific literacy. Recommendations include prototype development, pilot testing, and teacher training to ensure effective implementation. This study contributes to the growing body of literature on digital media in elementary science education within the Southeast Asian context.